1991
DOI: 10.1152/ajprenal.1991.260.6.f921
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine stimulates phosphate and glucose transport in opossum kidney epithelial cells

Abstract: We have examined the effects of adenosine on sodium-coupled phosphate and glucose transport in cultured opossum kidney (OK) cells, a continuous cell line that resembles proximal tubule. Adenosine analogues R-(-)-N6-phenylisopropyladenosine (PIA) and 2',5'-dideoxy-adenosine (DDA) were employed as adenosine A1 receptor and P site-selective agonists, respectively. Sodium-dependent phosphate uptake activity (Na-Pi symport) increased by approximately 25% above both basal and parathyroid hormone (PTH)-inhibited leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
2
22
2
Order By: Relevance
“…The observed diuresis and natriuresis in response to selective A 1 receptor blockade was caused by inhibition of proximal tubular reabsorption (Knight et al, 1993;van Buren et al, 1993;Wilcox et al, 1999). In accordance, in vitro studies in the proximal tubule showed that activation of A 1 receptor can stimulate transport of fluid, HCO 3 Ϫ as well as Na ϩ -glucose and Na ϩ -phosphate symport (Coulson et al, 1991;Takeda et al, 1993;Cai et al, 1994Cai et al, , 1995. The intracellular signaling pathways that contribute to these changes in tubular transport are still under investigation but may include reductions of intracellular cAMP levels (Kost et al, 2000), increases of intracellular Ca 2ϩ (Di Sole et al, 2003), and calcineurin homologous proArticle, publication date, and citation information can be found at http://jpet.aspetjournals.org.…”
supporting
confidence: 57%
“…The observed diuresis and natriuresis in response to selective A 1 receptor blockade was caused by inhibition of proximal tubular reabsorption (Knight et al, 1993;van Buren et al, 1993;Wilcox et al, 1999). In accordance, in vitro studies in the proximal tubule showed that activation of A 1 receptor can stimulate transport of fluid, HCO 3 Ϫ as well as Na ϩ -glucose and Na ϩ -phosphate symport (Coulson et al, 1991;Takeda et al, 1993;Cai et al, 1994Cai et al, , 1995. The intracellular signaling pathways that contribute to these changes in tubular transport are still under investigation but may include reductions of intracellular cAMP levels (Kost et al, 2000), increases of intracellular Ca 2ϩ (Di Sole et al, 2003), and calcineurin homologous proArticle, publication date, and citation information can be found at http://jpet.aspetjournals.org.…”
supporting
confidence: 57%
“…Elucidation of the renal tubular effects of adenosine is complicated by hormonally induced changes in hemodynamics and glomerular filtration rate that can mask direct effects of adenosine. Nevertheless, adenosine has been shown to antagonize vasopressin-stimulated water reabsorption in the cortical collecting duct (CCD)' (2) and inner medullary collecting duct (3), to stimulate Na+-phosphate and Na+-glucose transport in opossum kidney cells (4), and to inhibit the transepithelial voltage across isolated cortical thick ascending limbs of Henle's loop (5), suggesting a direct inhibitory action on sodium chloride reabsorption.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in opossum kidney cells (proximal tubular phenotype), activation of A 1 adenosine receptors increases Na ϩ -phosphate and Na ϩ -glucose symport (7), and in rabbit proximal convoluted tubules, stimulation of A 1 receptors accelerates Na ϩ -3HCO 3 Ϫ symport in the basolateral membrane (56). It is now firmly established that activation of A 1 receptors augments proximal tubular sodium reabsorption (30,31,59,63).…”
mentioning
confidence: 99%